Promoting intangible cultural heritage to promote identity: insights from the perceptions of the generation Z on the Southern Shaanxi folk songs of China - GuangChao, Liu; Fee, Lee Yok; Ab Razak, Ratna Roshida; Ab Majid, Arfah (Common Ground Research Networks, 2025)
Although the folk songs of Southern Shaanxi are an important part of China’s intangible cultural heritage (ICH), they face great difficulties in dissemination and preservation in the context of globalization and modernization. As the main force in spreading traditional culture, it is a pressing issue to better expose the Z generation to, and spread the folk songs of Southern Shaanxi through the education system, community cultural activities, and digital media platforms. Hanzhong and Ankang, two places rich in folk songs in Southern Shaanxi, are used as the background for this qualitative case study. Data were collected through participant observation, semi-structured interviews, and case analysis to explore how the Generation Z engages with folk songs and their perceptions of current transmission strategies. The study concluded that the Generation Z’s classroom experience and perception can be enhanced by integrating immersive and participatory teaching methods into the educational environment. It also recommends designing interactive community activities to strengthen inter-generational communication and encourage active participation from younger learners. In addition, developing digital media content that combines cultural depth with contemporary forms is essential to appeal to the Generation Z’s preferences and convey the unique cultural value of the Southern Shaanxi folk songs. Through these comprehensive strategies, practical solutions are provided for the dissemination and inheritance of the Southern Shaanxi folk songs in the context of modernization and globalization, and also provide reference significance for the protection and dissemination of other ICH.